2005
DOI: 10.1029/2004gl021044
|View full text |Cite
|
Sign up to set email alerts
|

Possible association between Indian monsoon rainfall and solar activity

Abstract: [1] Over the 120 y period for which reliable Indian rainfall statistics are available, solar activity parameters exhibit nonstationarity. Taking this fact into account, we present here the results of an analysis of four solar activity indices and seven major Indian monsoon rainfall time series, over two distinct test periods respectively of low and high solar activity, each comprising three complete solar cycles. It is found that the average rainfall is higher in all seven rainfall indices during periods of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
63
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(67 citation statements)
references
References 19 publications
4
63
0
Order By: Relevance
“…Lal et al, (2001) concluded that annual mean area-averaged surface warming over the Indian subcontinent to range between 3.5°C and 5.5°C over the region during 2080s, while the DEFRA (2005) suggested that for a warming of 2°C, the yields of both rice and wheat will fall in most places, with the beneficial effect of increased CO 2 being more than offset by the temperature changes over India; similar results have been found for soybean (Mall et al, 2004). Next Battacharya and Narasimha (2005) studied the possible association between Indian monsoon rainfall and solar activity. Ashrit et al, (2005) investigated the impact of anthropogenic climate changes on the Indian summer monsoon and the ENSO-monsoon teleconnection.…”
mentioning
confidence: 84%
“…Lal et al, (2001) concluded that annual mean area-averaged surface warming over the Indian subcontinent to range between 3.5°C and 5.5°C over the region during 2080s, while the DEFRA (2005) suggested that for a warming of 2°C, the yields of both rice and wheat will fall in most places, with the beneficial effect of increased CO 2 being more than offset by the temperature changes over India; similar results have been found for soybean (Mall et al, 2004). Next Battacharya and Narasimha (2005) studied the possible association between Indian monsoon rainfall and solar activity. Ashrit et al, (2005) investigated the impact of anthropogenic climate changes on the Indian summer monsoon and the ENSO-monsoon teleconnection.…”
mentioning
confidence: 84%
“…Kodera 2004) and from modern observational data (e.g. Mehta & Lau 1997;Bhattacharyya & Narasimha 2005;Maitra et al 2014;Chaudhuri et al 2015). However, a mechanism which could account for the reported relationships is unclear, although there are several possibilities: broadly, these mechanisms include so-called top-down solar UV irradiance effects, bottom-up total solar irradiance effects and relationships between atmospheric ionisation from the cosmic ray (CR) flux to aerosols and clouds (Gray et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Among the studies that examined multidecadal variations in Indian monsoon, some have investigated and suggested the multidecadal variation in the solar irradiance as a possible cause [e.g., Mehta and Lau, 1997;Neff et al, 2001;Agnihotri et al, 2002;Burns et al, 2002;Fleitmann et al, 2003;Kodera, 2004;Bhattacharyya and Narasimha, 2005;Berkelhammer et al, 2010]. Many of these studies show that the solar irradiance and monsoon intensity variations have been comparable in phase at decadal-centennial timescales.…”
Section: Introductionmentioning
confidence: 99%